Myth and image: ontological and epistemological dimensions of visual cognition (Journal of Philosophy Culture and Political Science, 2026)
This article examines the relationship between myth and visual art from the perspective of the philosophical nature of visual cognition. Myth is interpreted not as an archaic narrative form, but as an ontological structure that produces meaning and as an archetypal model of knowledge. Visual art, in turn, is conceptualized as the artistic representation of this structure and as an autonomous epistemological form of comprehending being.The study analyzes the works of A. Baktygerey, S. Bapyshev, S. Bektiyar, and B. Tulkiev, revealing how mythic archetypes and national codes are articulated and reinterpreted within contemporary visual language. The article brings the concepts of post-mythical consciousness, visual cognition, and the semantic structure of archetype and symbol into a philosophical discourse, and demonstrates the function of art as a meta-language that generates aesthetic, worldview-related, and existential meanings.Myth is thus presented as an alternative ontological–epistemological mode of understanding being through artistic representation, while the artistic image is regarded not merely as an aesthetic object, but as a philosophical structure that produces meaning. In this perspective, visual art appears not only as a cultural phenomenon, but as a specific philosophical mechanism for structuring experience and interpreting reality. The results contribute to contemporary philosophical and aesthetic theories of myth, symbol, and visual cognition, and provide a theoretical basis for interdisciplinary research in philosophy, art history, and cultural studies.Key words: myth, visual ontology, artistic representation, archetype, visual epistemology, cultural memory, post-mythical consciousness, representation of being.